2023
DOI: 10.3310/aqxc8219
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a social prescribing intervention in North East England on adults with type 2 diabetes: the SPRING_NE multimethod study

Abstract: Background Link worker social prescribing enables health-care professionals to address patients’ non-medical needs by linking patients into various services. Evidence for its effectiveness and how it is experienced by link workers and clients is lacking. Objectives To evaluate the impact and costs of a link worker social prescribing intervention on health and health-care costs and utilisation and to observe link worker delivery and patient engagement. Data sources Quality Outcomes Framework and Secondary Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 139 publications
0
1
0
Order By: Relevance
“…The high proportion of immigrants (around 30% of the department population) also accounts for the high proportion of patients whose mother tongue was not French. A cost-effectiveness evaluation conducted in a disadvantaged North England area among patients with type 2 diabetes showed that the highest benefit was seen among the most disadvantaged population [ 29 ]. This result shows that the SP/DC intervention in our university hospital could be similarly cost-effective given the deprivation level.…”
Section: Discussionmentioning
confidence: 99%
“…The high proportion of immigrants (around 30% of the department population) also accounts for the high proportion of patients whose mother tongue was not French. A cost-effectiveness evaluation conducted in a disadvantaged North England area among patients with type 2 diabetes showed that the highest benefit was seen among the most disadvantaged population [ 29 ]. This result shows that the SP/DC intervention in our university hospital could be similarly cost-effective given the deprivation level.…”
Section: Discussionmentioning
confidence: 99%